2020
DOI: 10.1101/2020.01.13.20017319
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Common genetic risk variants identified in the SPARK cohort implicate DDHD2 as a novel autism risk gene

Abstract: Background: Autism spectrum disorder (ASD) is a highly heritable neurodevelopmental disorder. Large genetically informative cohorts of individuals with ASD have led to the identification of three common genome-wide significant (GWS) risk loci to date. However, many more common genetic variants are expected to contribute to ASD risk given the high heritability. Here, we performed a genome-wide association study (GWAS) using the Simons Foundation Powering Autism Research for Knowledge (SPARK) dataset to identify… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 113 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…We first obtained GWAS summary statistics of various traits including cortical and subcortical brain structure [Grasby et al, 2020;Hibar et al, 2017;Satizabal et al, 2019]), neuropsychiatric disorders and cognitive phenotypes [Demontis et al, 2019;Howard et al, 2019;Liu et al, 2019;Matoba et al, 2020;Pardiñas et al, 2018;Ripke et al, 2013;Savage et al, 2018; Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014; Stahl et al, 2019;Watanabe et al, 2019;Wray et al, 2018], and anthropometric measurements [Yengo et al, 2018] (Supplementary Table 1). All of the GWASs were performed in European ancestries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We first obtained GWAS summary statistics of various traits including cortical and subcortical brain structure [Grasby et al, 2020;Hibar et al, 2017;Satizabal et al, 2019]), neuropsychiatric disorders and cognitive phenotypes [Demontis et al, 2019;Howard et al, 2019;Liu et al, 2019;Matoba et al, 2020;Pardiñas et al, 2018;Ripke et al, 2013;Savage et al, 2018; Schizophrenia Working Group of the Psychiatric Genomics Consortium, 2014; Stahl et al, 2019;Watanabe et al, 2019;Wray et al, 2018], and anthropometric measurements [Yengo et al, 2018] (Supplementary Table 1). All of the GWASs were performed in European ancestries.…”
Section: Resultsmentioning
confidence: 99%
“…Second, mechanistic insight, because those variants associated with an endophenotype also influence risk for neuropsychiatric disorders, endophenotype associations are informative about the mechanisms leading to risk for neuropsychiatric disorders. Genome-wide association studies (GWAS) have identified common genetic variants associated with many traits, including brain structure [Adams et al, 2016;Elliott et al, 2018;Grasby et al, 2020;Hibar et al, 2015;Hibar et al, 2017;Satizabal et al, 2019;Stein et al, 2012;Zhao et al, 2020] and risk for neuropsychiatric disorders [Demontis et al, 2019;Howard et al, 2019;Matoba et al, 2020;Pardiñas et al, 2018;Stahl et al, 2019]. GWAS results from large sample sizes allow for the comparison of common variant genetic architectures between traits [Watanabe et al, 2019] and the direct evaluation of these endophenotype properties.…”
Section: Introductionmentioning
confidence: 99%
“…Genome wide association studies (GWAS) have identified many common non-coding variants associated with risk for brain structure, neurodevelopmental disorders, and other brain-related traits [1][2][3][4][5][6][7] . However, it is challenging to determine the mechanism of non-coding variants because, in general, (1) the genes impacted by non-coding risk variants are unknown, (2) the cell type(s) and developmental period(s) where the variants have an effect are not known, (3) and there may be limited availability of tissue representing the causal developmental stage and cell type.…”
Section: Introductionmentioning
confidence: 99%